2018
DOI: 10.1097/jhq.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Family-Initiated Pediatric Rapid Response: Characteristics, Impetus, and Outcomes

Abstract: Family-initiated rapid response events were activated for legitimate concerns and frequently needed clinical interventions. Enhanced information and awareness of FIRR can improve utilization of the system and enhance family satisfaction, patient safety, and outcomes. Disseminating the information on FIRR and the importance of family involvement will improve the care of children and empower family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Evaluations to understand the effectiveness of these schemes 15,16 have indicated that on occasions relatives identified deterioration and escalated a number of patients that were undetected by healthcare staff 10,11,17–19 . Studies also identified that they are valued by patients and relatives 11,16,17,20 and are associated with increased feelings of reassurance and patient empowerment 11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations to understand the effectiveness of these schemes 15,16 have indicated that on occasions relatives identified deterioration and escalated a number of patients that were undetected by healthcare staff 10,11,17–19 . Studies also identified that they are valued by patients and relatives 11,16,17,20 and are associated with increased feelings of reassurance and patient empowerment 11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Confusion also arises from the variety of names that exist for the intervention. Family-initiated escalation of care [37], patient and family-initiated rapid response system [42], patient and relative-activated RRT [41] and family-initiated rapid response [43] are amongst those identified, with some appearing to promote both patient and family escalation [42] and others family escalation only [43]. It is therefore evident that greater clarity is needed in relation to what such systems/interventions should be called and who exactly they are intended for.…”
Section: Introductionmentioning
confidence: 99%
“…A number of evaluations have been carried out to understand how these interventions work in practice. These have focused on identifying the number of patient and family-initiated calls, the reasons for activation and identifying who escalates calls [33, 34, 40, 41, 43, 48, 49]. In the majority of cases, most of the reasons for activating escalation of care were cited as appropriate [36, 50].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations